Palestine: un féminisme de libération - Elia, Nada; Hammar, Liza; Dupuis-Déri, Francis (Les éditions du remue-ménage, 2024)
"Comment expliquer qu’Israël, malgré ses attaques meurtrières à Gaza et sa violation du droit international, reste à l’abri de toute véritable critique? Pourquoi de nombreuses féministes du Nord global, si promptes à dénoncer l’impact du «fondamentalisme islamique» sur les femmes palestiniennes, restent-elles silencieuses quand il s’agit de décrier l’occupation et le génocide que perpétue l’État israélien en Palestine? En déconstruisant les associations fallacieuses entre antisionisme et antisémitisme, la professeure et militante palestinienne Nada Elia, qui vit aujourd’hui aux États-Unis, rappelle la place des femmes et des personnes queers dans la lutte pour la libération de la Palestine, et revendique le démantèlement des structures coloniales qui écrasent la population à Gaza et en Cisjordanie."– Site de l'éditeur.
Section: 124 pages, 1 page non numérotée ; 14 cm.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; antisionisme; antisémitisme; approches et analyses; asie; cours; discipline; disicpline; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; militance; palestine; pol4212; premier cycle; privilèges; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Les femmes musulmanes ne sont-elles pas des femmes ? - Karimi, Hanane (Hors d'atteinte, 2023)
« Mes larmes étaient celles d'un désenchantement : un désenchantement féministe. J'avais échoué à trouver les mots qui auraient fait douter ces femmes de leur offensive contre d'autres femmes, de leur trahison d'un féminisme universel de leur aveuglement par des biais racistes et islamophobes. Puisque l'islamisme était l'ennemi, celles qui affichaient leur adhésion à l'islam devenaient à leurs yeux l'incarnation de ce danger, et se retrouvaient exclues des luttes pour les droits des femmes. Mais les femmes musulmanes ne sont-elles pas des femmes ? »–Page 4 de la couverture.
Section: 167 pages ; 20 cm
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; com5170; cours; discipline; droits des femmes*; europe; exclusion; france; féminisme islamique; islamophobie; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Chroniques d'une musulmane indignée - Ibnouzahir, Asmaa (Fides, 2015)
En plus d'un récit autobiographique racontant les défis qu'elle a relevés en tant que jeune immigrante musulmane d'origine marocaine arrivée au Québec en 1994, Asmaa Ibnouzahir présente également une analyse éclairante sur des questions qui reviennent souvent dans nos médias au sujet de l'islam, des femmes et de la société: les musulmans «modérés», les crimes «d'honneur», le foulard, le féminisme islamique et bien d'autres. Islamiste pour certains et hérétique pour d'autres, Asmaa Ibnouzahir partage avec nous son parcours personnel et militant qui a fait d'elle la citoyenne québécoise musulmane, féministe et indignée qu'elle est aujourd'hui. Engagée dans les débats sociopolitiques qui ont traversé le Québec au cours de la dernière décennie, sur la religion, l'immigration et les valeurs québécoises, Asmaa Ibnouzahir livre un témoignage essentiel qui donne un accès sans précédent aux coulisses de ces débats. Depuis une dizaine d'années, Asmaa Ibnouzahir est engagée dans la réflexion et les débats sociaux autour des droits de la personne, notamment sur les questions touchant autant à l'immigration et à la religion dans la sphère publique qu'au statut des femmes dans l'Islam. Elle a également voyagé et travaillé dans plus d'une quinzaine de pays en tant que spécialiste de la nutrition d'urgence humanitaire. – [Renaud-Bray].
Section: 367 pages ; 23 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; amériques; approches et analyses; canada; com5170; corps; cours; discipline; droits des femmes*; droits des personnes; féminisme islamique; immigration; maroc; point de vue situé; premier cycle; périodes historiques; québec; religion; régions géographiques; science politique; science politique et droit; thématiques

"Deveiling" Body Stories: Muslim Girls Negotiate Visual, Spatial, and Ethical "Hijabs" - Hamzeh, Manal (Race, Ethnicity and Education, 2011)
This article describes a collaborative research project that took place in two south‐western US border towns and sought to understand how four muslim Footnote 1 girls (age 14–17) expressed and negotiated their bodily learning experiences. Drawing on both the work of arab–muslim critical feminist Fatima Mernissi who utilized classical Islamic tools of research and my positionalities as arabyyah‐muslimah, I used insider’s methods to discuss how three hijabs (veils) – the visual, spatial, and ethical – acted as a central genderizing discourse that challenged the girls’ learning opportunities. This article shows how the girls’ parents enforced these three hijabs; how the girls questioned and deveiled the hijabs in their dress, mobility in public places, and physical behavior around boys. This inquiry is a call for critical feminist researchers and educators to recognize how these three hijabs form a key genderizing discourse in the lives of muslim girls. It also presents the importance of: (1) working with muslim girls as agents in their own lives; (2) critical engagement with difference between researchers/educators and muslim communities; and (3) practicing a critically reflexive pedagogy of deveiling.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; corps; cours; discipline; féminisme islamique; point de vue situé; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; thématiques; états-unis; états-unis (sud)

Honor killings in the Middle East and North Africa: a systematic review of the literature - Kulczycki, Andrzej; Windle, Sarah (Violence against women, 2011)
A systematic review of the research literature on honor killings in the Middle East and North Africa (MENA) indicates a paucity of studies relative to the presumed magnitude of the problem. Forty articles were reviewed and critically appraised, of which only 9 contained primary data and 11 presented original secondary analyses. Despite a recent increase in published studies, persistent methodological limitations restrict the generalizability of findings. Most studies focus on legal aspects, determinants, and characteristics of victims and perpetrators. Victims are mostly young females murdered by their male kin. Unambiguous evidence of a decline in tolerance of honor killings remains elusive.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; cours; droits des femmes*; féminisme islamique; maghreb; moyen-orient; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sex2283; sexisme; systèmes d'oppressions; thématiques; violences

Les monologues voilés (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Place: Paris Publication Title: Scènes & Cies
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte

Engaging islamic feminism: Provincializing feminism as a master narrative - Barlas, Asma (Islamic feminism: Current perspectives, 2008)
https://images.shulcloud.com/14262/uploads/Jeannettes-Class-Documents/WeekThree/EngagingIslamicFeminism.pdf
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discours dominant; fem3400; féminisme islamique; premier cycle; périodes historiques; ressource en ligne; systèmes d'oppressions

Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis

Unveiled Sentiments: Gendered Islamophobia and Experiences of Veiling among Muslim Girls in a Canadian Islamic School - Zine, Jasmin (Equity & Excellence in Education, 2006)
The practice of veiling has made Muslim women subject to dual oppressions–racism and Islamophobia–in society at large and patriarchal oppression and sexism from within their communities. Based on a narrative analysis of the politics of veiling in schools and society, the voices of young Muslim women attending a Canadian Islamic school speak to the contested notion of gender identity in Islam. The narratives situate their various articulations of Islamic womanhood in ways that both affirm and challenge traditional religious notions. At the same time they also are subject to Orientalist representations of veiled and burqa clad women that represent them as oppressed and backward. Focusing on ethnographic accounts of veiling among Muslims girls who attended a gender-segregated Islamic high school in Toronto, this discussion allows a deeper understanding of how gendered religious identities are constructed in the schooling experiences of these Muslim youth. (Contains 11 notes.)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; corps; cours; discipline; féminisme islamique; intersectionnalité; islamophobie; ontario; patriarcat; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; toronto; voiles islamiques